2019
DOI: 10.1038/s41598-019-50071-w
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemical examination of transthyretin (TTR) brain penetration assisted by iododiflunisal, a TTR tetramer stabilizer and a new candidate drug for AD

Abstract: It is well settled that the amyloidogenic properties of the plasma protein transporter transthyretin (TTR) can be modulated by compounds that stabilize its native tetrameric conformation. TTR is also present in cerebrospinal fluid where it can bind to Aβ-peptides and prevent Aβ aggregation. We have previously shown that treatment of Alzheimer’s Disease (AD) model mice with iododiflunisal (IDIF), a TTR tetramer stabilizing compound, prevents AD pathologies. This evidence positioned IDIF as a new lead drug for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 53 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…In a revealing experiment, and using an AD transgenic mouse model with TTR genetic reduction (AD/TTR+/-), it was reported that IDIF administration resulted in decreased amyloid burden and total Aβ brain levels, and in the improved cognitive function of the animals [102]. Importantly, recent data showed that the TTR/IDIF complex exhibits improved BBB permeability, as compared to TTR and IDIF alone [103], providing higher Aβ sequestering capacity, and adding to the therapeutic potential of TTR in AD. In a different work, administration of resveratrol, to the AD/TTR+/-mouse model, also produced decreased brain Aβ burden and raised plasma TTR concentrations [104], confirming the stabilization hypothesis, whereas administration of resveratrol to a different AD mouse model, although not inducing decreased plaque burden, increased TTR protein concentration in the brain [105].…”
Section: Transthyretin As Therapeutic Target In Alzheimer's Diseasementioning
confidence: 99%
“…In a revealing experiment, and using an AD transgenic mouse model with TTR genetic reduction (AD/TTR+/-), it was reported that IDIF administration resulted in decreased amyloid burden and total Aβ brain levels, and in the improved cognitive function of the animals [102]. Importantly, recent data showed that the TTR/IDIF complex exhibits improved BBB permeability, as compared to TTR and IDIF alone [103], providing higher Aβ sequestering capacity, and adding to the therapeutic potential of TTR in AD. In a different work, administration of resveratrol, to the AD/TTR+/-mouse model, also produced decreased brain Aβ burden and raised plasma TTR concentrations [104], confirming the stabilization hypothesis, whereas administration of resveratrol to a different AD mouse model, although not inducing decreased plaque burden, increased TTR protein concentration in the brain [105].…”
Section: Transthyretin As Therapeutic Target In Alzheimer's Diseasementioning
confidence: 99%
“…This is not surprising, since some studies show differences in the amount of TTR in different brain regions(58).Furthermore, our recent PET-imaging study shows that entrance of TTR into the brain after intravenous administration starts at the third ventricles, which suggests that TTR traffic occurs partially via the cerebrospinal fluid-brain barrier (CSFBB) and not only through the blood brain barrier (BBB)(37). Ultimately, this led to lower and delayed TTR presence in peripheral areas of the brain(37), such as CTX, where a significant concentration of TTR could be observed only at 6 hours after administration. Assuming the same transport mechanism of IDIF-and tolcapone-stabilized TTR this delay could be one of the reasons for insufficient influx of the complex into CTX.…”
mentioning
confidence: 84%
“…One of these compounds, iododiflunisal (IDIF; Figure 1) has proven efficient in promoting Aβ clearance from the brain and improving animal's cognitive functions when orally administered to AD transgenic mice (AβPPswe/PS1A246E/TTR+/-) daily for 2 months, starting just before the onset of the disease (36). Another study showed that the formation of TTR-IDIF complex enhances brain penetration of both TTR and IDIF (37).…”
Section: Introductionmentioning
confidence: 99%
“…Among known TTR mutants, the V30M [7] and the Y78F [8] are the most common FAP mutation and the most amyloidogenic, respectively. Moreover, the importance of TTR stability also concerns neurodegenerative disorders such as Parkinson's and Alzheimer's diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Over time, a large number of SAR studies have been published in order to identify typical substructures which are shared by compounds that stabilize TTR tetramer [3,[34][35][36][37][38][39]. In this field, the potential of iodine as substituent (iodination hypothesis) has been intensively explored through evaluating the inhibition ability of iodinated compounds with respect to non-iodinated analogues [10,11,17,36,[40][41][42][43]. Among iodinated motifs, 2,4,6-triiodophenol proved to be one of the most potent TTR fibrillogenesis inhibitor known so far [11], and iododiflunisal was shown to stabilize TTR [17].…”
Section: Introductionmentioning
confidence: 99%